Workplace Safety Culture Maturity: Application of the Hudson Model in a Dairy Plant in Southwestern Paraná - Buffon, Gabriela (2018)
This study aimed to analyze the degree of maturity of safety culture at work in the operational sector of a dairy plaint located in Paraná Southwest. With quantitative nature, the approach made use of closed questionnaire based on the model of safety culture maturity analysis proposed by Hudson (2001 apud Gonçalves, 2011), applied to a sample of forty-seven operational employees and three managers of the safety area and prevention of dairy work accidents. As the study results, operational officials attribute the degree of safety culture maturity at work on "sustainable" stage. As for management, the stage of maturity of safety culture at work is on stage "proactive". Finally, it is shown as plaintiffs improvement actions aimed at repositioning the factors 'involvement' and "organizational learning" among the stages of maturity of safety at work in the company.